POST-CAMBRIAN CLOSURE OF THE DEEP-WATER SLOPE-BASIN TAPHONOMIC WINDOW - Orr P.J.; Benton M.J.; Briggs D.E.G. (My University, 2003)
Exceptional faunas (Konservat-Lagerstaatten that preserve traces of volatile nonmineralized tissues) are statistically overabundant in the Cambrian Period; almost all examples preserved in continental-slope and shelf-basin environments are of this age. The hypothesis that an increase in the amount and complexity of bioturbation was an important agent in the elimination of this deep-water slope-basin taphonomic window is supported. Post-Cambrian ichnofaunal assemblages contain a higher proportion of pascichnia and agrichnia, ethologies produced by a mobile infauna. They also illustrate the lateral partitioning of organisms into different environmental niches; both opportunistic and equilibrium infaunas occur in low-oxygen environments in which the preservation of nonbiomineralized tissues was favored. Direct consumption of carcasses by bioturbating organisms was less important than changes to sediment properties as a result of bioturbation, notably enhanced microbial degradation of reactive organic matter, increased permeability, and the disruption of geochemical gradients necessary for mineral authigenesis. [PERIODICAL ABSTRACT]
Keywords: GEOLOGY; Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская